1996
DOI: 10.1159/000184821
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glia in the Neuroendocrine Hypothalamus: Possible Implications in Hormone Secretion

Abstract: Recent evidence indicates that glia may play a significant role in the link between the endocrine and nervous systems. Gonadal steroids modulate astroglia morphology, differentiation and gene expression in different brain areas. Hormonal effects on glia may have important consequences for neuronal development, metabolism and activity, for the formation and plasticity of synaptic connections, and for the modulation of hypothalamic hormone release. Perinatal and adult testosterone levels modulate the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…These astrocytes express GFAP and/or vimentin/S100␤ (Mercier and Hatton, 2000). The role of glia in neuroendocrine secretion also has been suggested by Chowen et al (1996). Horner et al (2000) recently reported that the majority of dividing progenitor cells of the adult spinal cord resides in the outer circumference (subpial zone).…”
Section: Prevalence Of Cx26 In the Meninges And In Subpial And Subepementioning
confidence: 85%
“…These astrocytes express GFAP and/or vimentin/S100␤ (Mercier and Hatton, 2000). The role of glia in neuroendocrine secretion also has been suggested by Chowen et al (1996). Horner et al (2000) recently reported that the majority of dividing progenitor cells of the adult spinal cord resides in the outer circumference (subpial zone).…”
Section: Prevalence Of Cx26 In the Meninges And In Subpial And Subepementioning
confidence: 85%
“…The endocrine system and the nervous system are closely related with both neurons and glia contributing to the link between two systems (Chowen et al, 1996 ; Garcia-Segura et al, 1996 ; Noda, 2015 ; Morita et al, 2019 ). In the adult central nervous system (CNS), thyroid dysfunction triggers psychological conditions such as anxiety and depression (Paschke et al, 1990 ; Suwalska et al, 2005 ; Gulseren et al, 2006 ), and patients with attention-deficit/hyperactivity disorder have greater comorbid rates with hyperthyroidism (Chen et al, 2018 ; Zader et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%